The Effect of Learning Interest and Facilities on Students’ Learning Outcomes in Economics At SMA Negeri 2 Sukoharjo - Sri Susanna Sembiring; Titik Ulfatun; Dewi, Rahmatika (Universitas Muhammadiyah Surakarta, 2023)
The success of educational goals is frequently determined by the quality of the learning outcomes. The students’ learning outcomes are influenced by a number of factors. The objectives of this study are to: 1) investigate the effect of learning interest on students’ learning outcomes in Economics of class XI Social Science at SMA Negeri 2 Sukoharjo; 2) investigate the effect of learning facilities on students’ learning outcomes in Economics of class XI Social Science at SMA Negeri 2 Sukoharjo; and 3) investigate the effect of learning interest and learning facilities on students’ learning outcomes in Economics of class XI Social Science at SMA Negeri 2 Sukoharjo. This quantitative study used a total sample size of 106 students of grade XI Social Science at SMA Negeri 2 Sukoharjo. This study was carried out by distributing questionnaires to the students to collect the data. Data analysis technique used multiple regression analysis. The results of this study indicate that 1) learning interest has a significant effect on students’ learning outcomes in Economics of class XI Social Science at SMA Negeri 2 Sukoharjo; 2) learning facilities have no significant effect on students’ learning outcomes in Economics of class XI Social Science at SMA Negeri 2 Sukoharjo; and 3) learning interest and learning facilities simultaneously have a significant effect on students’ learning outcomes in Economics of class XI Social Science at SMA Negeri 2 Sukoharjo.